Enhancement of Supply Chain Control Tower to Reduce Inventory Parts of Heavy Equipment at PT XYZ - Dwiyana, Meidi; Dyah Kusumastuti, Ratih; Bustaman, Yosman (Riviera Publishing, 2022)
Introduction: As a leading heavy equipment distributor in Indonesia, PT XYZ is very concerned about after-sales service as an advantage compared to competitors. Keeping the service level based on target was accompanied by a decrease in working capital as one of the goals of PT. XYZ was establishing a tower in its supply chain concept. This research was conducted at PT. XYZ owns the largest market share of heavy equipment in Indonesia. The purpose of this study was to analyze the increase in the supply chain control tower in reducing the inventory of heavy equipment spare parts at PT. XYZ. Method: This research uses mixed methods, a stage of research combining two types of research methodologies, namely qualitative and quantitative. Result: The analysis results at SCOR level 1 show that all strategic metrics are below the set targets. So that at SCOR level 2, an in-depth analysis is carried out with Geographic maps and Thread diagrams that show potential problems in Enable Process (sE2), Plan Source (sP2) and Delivery (sD1) activities. Finally, the results of SCOR level 3 analysis using a fishbone diagram reveal that the root cause of the problem is a leak in internal company supply chain management. We recommend the enhancement of the supply chain control tower at PT XYZ. Conclusion: This Research primarily aims to evaluate the element supply chain control tower at PT XYZ as a stocked business product with SCOR Model 12.0. The result shows that the performance of the Supply Chain Control Tower in Tower Tanjung Area (TAD) does not achieve the target.